Memoriał dr. Emila Sommersteina i opinia prawna dr. Michała Szuldenfreia – krytyczna edycja źródeł o statusie prawnym ludności polskiej w ZSRR (1944 r.) - Marciniak, Wojciech (Instytut Historii PAN, 2025)
The article presents early concepts for regulating the citizenship of the Polish population in the USSR, primarily focusing on those who were victims of Soviet repressions between 1939 and 1941. Their authors were active members of the Union of Polish Patriots and of the administration of Poland staff subordinated to the Soviets (the Polish Committee of National Liberation, National Council). The study focuses on the two documents created in 1944 – during the period when the Kremlin issued important legal acts concerning the Polish population (decisions of the Presidium of the Supreme Soviet of the USSR on the restoration of Polish citizenship and amnesty), and when the Polish Committee of National Liberation concluded agreements on resettlement with the neighbouring Soviet republics.
p. 221-241
Summary in English.
Keywords: repatriation from the USSR; Polish citizenship; Polish Committee of National Liberation; Union of Polish Patriots in the USSR; history of Polish administration; Polish--Soviet relations; Poles - Soviet Union - 1900-1945; Poles - Soviet Union - 1945-1970